Dangerous trade. Histories of industrial hazard across a globalizing world (Philadelphia, 2011)
"From anthrax to asbestos to pesticides, industrial toxins and pollutants have troubled the world for the past century and longer. Environmental hazards from industry remain one of the world's foremost killers. Dangerous Trade establishes historical groundwork for a better understanding of how and why these hazards continue to threaten our shrinking world. In this timely collection, an international group of scholars casts a rigorous eye toward efforts to combat these ailments. Dangerous Trade contains a wide range of case studies that illuminate transnational movements of riskofrom the colonial plantations of Indonesia to compensation laws in late nineteenth century Britain, and from the occupational medicine clinics of 1960s New York City to the burning of electronic waste in early twenty-first century Uruguay. The essays in Dangerous Trade provide an unprecedented broad perspective of the dangers stirred up by industrial activity across the globe, as well as the voices raised to remedy them."